(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present article is an attempt to explore the role of employee assistance programs to resolve the challenges like Globalization, Managing the value chain, Business competitiveness, increasing profitability, capability focus, technology, organizational change faced by human resources in an organization. EAPs are intended to help employers, typically in conjunction with a health insurance plan. EAPs are intended to help employees deal with personal problems that might adversely impact their work performance, heath and well being. Employee Assist Programs generally includes assessment, short-term counseling and referral services for employees and their household members.